Projeto comparativo de smart plug para monitoramento de aparelhos eletricos residenciais - Sena, Pedro Paulo Aires de (Universidade Federal Rural do Semi-Árido, 2021)
Brazilian residential energy consumers, classified in group B by the ANEEL standard, act as passive agents when the topic discussed is related to the control of energy consumption in their own homes, since the energy meters installed in their input standards energy connections are owned by energy companies and only these companies have full access to their customers' consumption patterns. Although this is relevant information, especially when it comes to making changes and adopting alternatives to the high values of electricity consumption, consumers in this group have little or no information that can help them in the process of getting to know their habits and consumption patterns. In addition, as it is a process that uses specific equipment and that sometimes requires a qualified professional to handle it correctly, obtaining specific knowledge on this topic makes this process expensive and often inaccessible to the general population. Thus, with a view to providing residential consumers with a means to monitor the consumption of their electrical equipment in a simplified way, with easy installation and easy access to information, for this work a simulated project of an intelligent device for measuring quantities was carried out for use by residential consumers. This device was based on other similar devices developed in academic research and also professional commercial energy analyzers to verify its operation, which, for the loads tested and compared, presented satisfactory results in comparison with the other equipment mentioned. The device developed in a simulation will also serve as a basis for future work, with its physical development for tests in real residential environments
Keywords: Medidor inteligente; Consumo de energia; Monitoramento de consumo; Consumidor residencial; Smart meter; Energy consumption; Consumption monitoring; Residential consumers; ENGENHARIAS::ENGENHARIA ELETRICA